Antibiotic activities of the natural antimicrobial substance produced by Lactobacillus paracasei FX-6 against Pseudomonas putida. (April 2020) - Duan, Xingxing; Chen, Siyu; Duan, Shan; Lan, Chunmin; Yang, Zhennai; Cao, Yong; Miao, Jianyin
Abstract: In our previous study, Lactobacillus paracasei FX-6 was isolated from kefir, and the antimicrobial substance produced by FX-6 had broad spectrum antimicrobial activity, which had a good effect of preservation on chicken breast and could significantly inhibit the dominant spoiled bacteria Pseudomonas. In this study, we isolated and identified the dominant bacteria Pseudomonas, and we also researched the antibacterial effect and mechanism of antibacterial substance against Pseudomonas . The dominant bacteria Pseudomonas was isolated from spoiled chicken breast meat and identified as Pseudomonas putida . The result showed that the minimum inhibitory concentration (MIC) of antibacterial substance against Pseudomonas putida was 12.5 mg/mL. The Propidium iodide (PI) infiltration experiments and leakage of potassium ions indicated the antimicrobial substance could increase the permeability of the bacterial cell membrane. Scanning electron microscope (SEM) revealed that the antimicrobial substance damaged the morphology of Pseudomonas putida cell. Result of sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) suggested that the synthesis of protein of Pseudomonas putida could be affected by the antibacterial substance. The result of agarose gel retardation indicated that the genomic DNA could be combined with the antimicrobial substance. Highlights: Antibiotic activities of the antimicrobial substance were evaluated. Antimicrobial substance increased membrane permeability. Antimicrobial substance could affect the synthesis of protein. Antimicrobial substance was able to bind genomic DNA.